2020
DOI: 10.1108/tqm-05-2020-0118
|View full text |Cite
|
Sign up to set email alerts
|

Gamification and service quality in bike sharing: an empirical study in Italy

Abstract: PurposeBike sharing (BS) is a phenomenon of growing interest in the sustainable mobility field. In recent years, many governments have implemented concrete actions to diffuse the services in cities, trying to encourage citizens' sustainable behavior. Several mobile applications (apps) related to the mobility sector have embedded gamification mechanics applied in non-gaming contexts, able to create and increase user engagement and to manage users' behavior (Deterding et al., 2011). The main purpose of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 106 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…The findings of this research indicate that Gamification, taken as a whole, has a large and beneficial impact on individuals' innate motivations. Both Mekler et al (2017) and Pasca et al, (2021) share the same view on the reliability of the outcomes of the studies. In the context of this study, a game on Tokopedia represents the application of "game thinking" in gaming.…”
Section: A the Gamification Effect Towards Intrinsicmentioning
confidence: 97%
“…The findings of this research indicate that Gamification, taken as a whole, has a large and beneficial impact on individuals' innate motivations. Both Mekler et al (2017) and Pasca et al, (2021) share the same view on the reliability of the outcomes of the studies. In the context of this study, a game on Tokopedia represents the application of "game thinking" in gaming.…”
Section: A the Gamification Effect Towards Intrinsicmentioning
confidence: 97%
“…By acknowledging the lack of research on gamified services, scholars such as Wolf et al (2018) studied gamified e-services and indicated that gamified services can influence customers to reuse them. Likewise, Pasca et al (2020) demonstrated the adoption of gamification in bicycle-sharing applications with their impacts on improving service quality, the users' loyalty and promoting bicycle-sharing systems in Italy. Numerous studies conducted on the impact of service quality on relationship quality dimensions, such as satisfaction (Rajaguru, 2016), loyalty (Orel and Kara, 2014) and behavioral tendencies (Orel and Kara, 2014).…”
Section: H2 Ge-sq Positively Influences Purchase Intentionmentioning
confidence: 99%
“…Most of the literature highlighted the behavior change as a crucial advantage, where it is possible to motivate users to have a more sustainable behavior (Blohm & Leimeister, 2013;Bucher & Kreisler, 2020) and co-design Loizou et al, 2019). A gamification approach is able to satisfy needs, enforce autonomy and competence (Xi & Hamari, 2019), improve the service quality and loyalty (Pasca et al, 2020), increase the sustainability performance in terms of energy and water consumption (AlSkaif et al, 2018), reduce CO2 emissions, encourage social collaboration (Albertarelli et al, 2018), among other aspects. In contrast, there are several disadvantages to use gamification (Lister et al, 2014;Petridis et al, 2014), e.g., the overuse of physical rewards might cause that players focus on the rewards instead of having a sustainable behavior (Wells et al, 2014), causing the unbalanced situation of having high effort and low results in the process (Gangolells et al, 2020).…”
Section: Advantages and Disadvantages Of Using A Gamification Approac...mentioning
confidence: 99%